AnxA5 reduces plaque inflammation of advanced atherosclerotic lesions in apoE−/− mice. Issue 10 (12th September 2014) - Burgmaier, Mathias; Schutters, Kristof; Willems, Brecht; van der Vorst, Emiel P.C.; Kusters, Dennis; Chatrou, Martijn; Norling, Lucy; Biessen, Erik A.L.; Cleutjens, Jack; Perretti, Mauro; Schurgers, Leon J.; Reutelingsperger, Chris P.M.
Abstract Annexin A5 (AnxA5) exerts anti‐inflammatory, anticoagulant and anti‐apoptotic effects through binding cell surface expressed phosphatidylserine. The actions of AnxA5 on atherosclerosis are incompletely understood. We investigated effects of exogenous AnxA5 on plaque morphology and phenotype of advanced atherosclerotic lesions in apoE−/− mice. Advanced atherosclerotic lesions were induced in 12 weeks old Western type diet fed apoE−/− mice using a collar placement around the carotid artery. After 5 weeks mice were injected either with AnxA5 (n = 8) or vehicle for another 4 weeks. AnxA5 reduced plaque macrophage content both in the intima (59% reduction, P < 0.05) and media (73% reduction, P < 0.01) of advanced atherosclerotic lesions of the carotid artery. These findings corroborated with advanced lesions of the aortic arch, where a 67% reduction in plaque macrophage content was observed with AnxA5 compared to controls (P < 0.01). AnxA5 did not change lesion extension, plaque apoptosis, collagen content, smooth muscle cell content or acellular plaque composition after 4 weeks of treatment as determined by immunohistochemistry in advanced carotid lesions. In vitro, AnxA5 exhibited anti‐inflammatory effects in macrophages and a flow chamber based assay demonstrated that AnxA5 significantly inhibited capture, rolling, adhesion as well as transmigration of peripheral blood mononuclear cells on a TNF‐α‐activated endothelial cell layer. In conclusion, short‐term treatment with AnxA5 reduces plaque inflammation of advanced lesions in apoE−/− mice likely through interfering with recruitment and activation of monocytes to the inflamed lesion site. Suppressing chronic inflammation by targeting exposed phosphatidylserine may become a viable strategy to treat patients suffering from advanced atherosclerosis.